Analisis Faktor-Faktor yang Mempengaruhi Hiperaktif Anak Kelas 4 di SDN Ciluluk II - Leni Nadiah; Levy Rohmatilahi; Muhammad Luthfi Setyawan Anshory; Deti Rostika; Ranu Sudarmansyah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Hyperactive behavior in grade 4 children at SD Ciluluk is a very complex challenge for educators which requires an in-depth understanding of the factors that influence it. Hyperactive behavior is an attitude in which every activity is carried out excessively or cannot control behavior in the environment within it. Believing that children become rubber feet is primarily due to biological and psychological factors. This research focuses on analyzing the factors that cause hyperactive children's behavior, highlighting biological and psychological aspects, thoroughly discussing the opinions of experts regarding hyperactive children, as well as the treatment of hyperactive children implemented by grade 4 teachers at Ciluluk Elementary School. This research aims to provide in-depth insight into the factors that can influence hyperactive behavior in grade 4 children at Ciluluk Elementary School. The expected results will certainly provide insight and solutions for hyperactive children in learning activities, especially in elementary schools, which will later be used as a reference for teachers to understand solutions for hyperactive children.